Analysis of incidence of caesarean sections in primigravida - Joshi, Suyujna D.; Rai, Rajeshwari; Banu, Ruksar; G., Jayasakthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Current study was conducted to determine the incidence of caesarean sections in primigravida. Methods: A total number of 1698 primigravidas were admitted in the department of DNB district hospital Ballari, out of which 501 primigravidas who underwent caesarean section were included in the study. Results: Caesarean section rate in primigravida was observed to be 29.5%, 55% of women were from rural areas and 45% from urban areas, 69.9% women belonged to lower class 31.1% belonged to upper middle class, 25% were illiterate while 75% were literate. Conclusions: Meta-analysis suggests that the occurrence of pregnancy complications differ according to fetal sex with a higher cardiovascular and metabolic load for the mother in the presence of a male fetus.